KINERJA KEUANGAN BANK SYARIAH DAN BANK KONVENSIONAL - Mas'ud, Imam (Universitas Muhammadiyah Jember, 2018)
The purpose of this research is measure level of financial performance of PT. Bank Syariah Mandiri, PT Bank Tabungan Pensiunan Nasional Tbk, and PT. Bank Mandiri in 2016-2017. Analysis have done include five components of financial ratios: (1) capital adequacy ratio, (2) non-performing loan, (3) return on asset and return on equity, (4) efficiency ratio and (5) loan to deposit ratio. This research is descriptive research which explaining comparison of ratio capital, asset, quality, management, earning, and liquidity. The result show PT. Bank Syariah Mandiri better than other in capital adequacy ratio and loan to deposit ratio. PT Bank Mandiri have better financial performance in asset, management, and earnings ratio. Keywords: Capital, Asset, Management, Earnings, Liquidity, Sharia Bank